Можливості впровадження еджайл-управління бізнесу в міжнародних інжинірингових компаніях - Чайкова, Олена Ігорівна; Вакерін, Павло Віталійович (НТУ "ХПІ", 2017)
У статті розглянута проблематика сучасного стану інжинірингових компаній України. Розглянуті основні постулати еджайлу, як адаптивної моделі управління, та його сучасні тенденції у світі. Вказуються умови, що найбільш підходять, для адаптивної моделі; перераховуються принципи адаптивної моделі. Обґрунтовується тезис про те, що адаптивну модель еджайл можна запровадити в інжинірингових компаніях, що дасть можливість виробляти інноваційні рішення в нестандартних ситуаціях. Розглянуті передумови для розробки адаптивної еджайл-моделі в інжинірингу.

The article reviews the current state of engineering companies in Ukraine. The basic tenets of agile as adaptive management model and its current trends in the world are considered. Most suitable conditions for adaptive model are pointed out; the principles of adaptive model; advantages and challenges faced by companies that have implemented agile-model are listed. Examples of the introduction and application of agile management in different branches are given. The thesis that agile-approach could be implemented in engineering companies, which would allow to produce innovative solutions in unusual situations, is grounded. Conditions for adaptive agile-model development in engineering are considered (based on the comparison of the agile in IT). The possibilities of creating engineering agile-teams and the principles of their work and interaction are considered.
Possibilities of introduction of agile-management by international engineering companies
Keywords: інжиніринг; технічні рішення; еджайл-підхід; фірми професійних послуг; ФПП; technical solutions; agile-approach